Recovery from Binge Eating Disorder - Krentz, Adrienne; Chew, Judy; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to characterize the psychological processes of recovery from binge eating disorder (BED). A model was developed by asking the research question, “What is the experience of recovery for women with BED?” Unstructured interviews were conducted with six women who met the DSM-IV criteria for BED, and who were recovered from binge eating for a minimum of six months. The model consists of the core category, Self-Awakening, and four phases, Self-Reflecting, Assessing Present Life Situation, Healing/Restoring Oneself, and Creating Balance. The main psychological processes of each phase are outlined and implications for counselling women with BED are discussed.